Influence of patient age and colorectal polyp size on histopathology findings - SILVA,Silvana Marques e (2014)
BACKGROUND: Colorectal cancer is a major cause of morbidity and mortality and can arise through the adenoma-carcinoma sequence. Colonoscopy is considered the method of choice for population-wide cancer screening. AIM: To assess the characteristics of endoscopically resected polyps in a consecutive series of patients who underwent colonoscopy at a university hospital and compare histopathology findings according to patient age and polyp size. METHODS: Retrospective, cross-sectional of 1950 colonoscopy reports from consecutively examined patients. The sample was restricted to reports that mentioned colorectal polyps. A chart review was carried out for collection of demographic data and histopathology results. Data were compared for polyps sized ≤0.5 cm and ≥0.6 cm and then for polyps sized ≤1.0 cm and ≥1.1 cm. Finally, all polyps resected from patients aged 49 years or younger were compared with those resected from patients aged 50 years or older. RESULTS: A total of 272 colorectal polyps were resected in 224 of the 1950 colonoscopies included in the sample (11.5%). Polyps >1 cm tended to be pedunculated (p=0.000) and were more likely to exhibit an adenomatous component (p=0.001), a villous component (p=0.000), and dysplasia (p=0.003). These findings held true when the size cutoff was set at 0.5 cm. Patients aged 50 years or older were more likely to have sessile polyps (p=0.023) and polyps located in the proximal colon (p=0.009). There were no significant differences between groups in histopathology or presence of dysplasia. CONCLUSION: Polyp size is associated with presence of adenomas, a villous component, and dysplasia, whereas patient age is more frequently associated with sessile polyps in the proximal colon.